Pengaruh Bahasa Indonesia Terhadap Pendidikan Karakter Mahasiswa DIII Keperawatan Sutopo Surabaya - Andini Eka Ardianti; Bella Fernanda Hasan; Nadiyah Fitrotul Millah; Silviatul Nur Asizah; Vicka Felysia Gadhis Blora; Eni Nurhayati (LPPM Politeknik Pratama, 2023)
Indonesian is a language that meets communication factors. In communicating, you can use the language skills you have mastered. So, the influence of Indonesian on character education for students will be very influential and have positive impacts, including preserving national culture, increasing feelings of love for the country, being able to know what is good and what is not according to culture, increasing one's potential and broadening one's horizons, especially insight into the importance of character education (Character Building) if students already have this knowledge. Indonesian is a language that fulfills communication factors. In communicating, you can use the language skills you have mastered. So, the influence of Indonesian on character education for these students will be very influential and have positive impacts, including preserving national culture, increasing feelings of love for the country, being able to know what is good and what is not according to culture, increasing one's potential and broadening one's horizons, especially insight into the importance of character education (Character Building) if students already have this knowledge